Effect of chromium substituted on structural and magnetic characterization lithium ferrite nanoparticles - Lan, Nguyen Thi; Tam, Phuong Dinh; Duong, Nguyen Phuong; Hien, Than Duc (Vietnam Journal of Chemistry, 2017)
In this work, we present a structural, morphology and magnetic study of the Li0.5Fe2.5-xCrxO4 spinel nanoparticles (x = 0, 0.5, 0.75, 1, and 1.25) with mean particle size of 20-30 nm prepared by sol-gel method. The lattice constants and the size of particle decrease with increasing Cr concentration. In these samples, the preference of Cr3+ and Li+ ions in the octahedral sites and a small degree of site-interchange between Li+ in the octahedral sites and Fe3+ in the tetrahedral sites were found which increases with increasing the Cr content. A decrease of magnetization due to the spin disorder in the surface layer of the particles was observed. The spontaneous magnetization at 5K suggests the Néel type of magnetic ordering in these samples. The magnetic coercivity is discussed in terms of particle size, morphology and chromium substitution. Keywords. Chromium substitution, sol-gel method, nanoparticles, lithium ferrite.